After Secularism - Wilson, E. author. aut Link
VIII, 222 p.
Keywords: Having destabilized dominant assumptions about the nature of religion, there is now a need to develop new ways of thinking about this ever-present phenomenon in global politics. This book outlines a new approach to understanding religion and its relationship with politics in the West and globally for International Relations.